Biogeoquímica de Ferro e Enxofre em Solos de um Manguezal no Contexto Semiárido Cearense (Acaraú) - Lopes, Camila Campos (2011)
Mangroves ecosystems are complex and have a dynamic marked by the interaction of several factors, both biotic (vegetation, macrobiotics), and abiotic (temperature, rainfall, tidal range). The interaction of these factors influences directly the physicalchemical and biological environment, reflected in parameters such as pH and Eh. In mangrove areas, as conditions hydromorphism cause the prevailing form of procurement of energy is the bacterial sulfate reduction, which is directly related to the iron cycle of these locations. Given this, we see the need for further studies in this branch of Soil Science, in view of the processes involved in these places are still poorly understood, especially in mangrove areas in semiarid climate. Since the estuary of the river Acaraú – CE an area within this context and with marked seasonality, a study of soil and pore water of this area was conducted with the aim of evaluating the behavior of iron and sulfur species, taking into account parameters such as seasonal variation in the region, depth and presence or absence of vegetation, and microbial activity. To obtain a detailed study of soils, soil pH, Eh, organic matter content, sulfate and chloride in pore water, salinity, sequential extraction of iron and respirometry were done in three areas of mangrove river Acaraú predominantly plant the genus Rhizophora and Avicennia, as well as a non-vegetated area. Overall, our data show that mangrove areas are slightly acidic or even alkaline environments and are strongly reducing. Among the fractions analyzed for iron, it is observed that their concentrations vary between areas, since the physicochemical conditions prevailing at the sampling points chosen are different. Furthermore, we observed that the transition from rainy to dry season promotes a greater accumulation of salts in the soil, as evidenced by increases in ion concentrations and salinity. In this context, the increased rate of evapotranspiration emerges as a determinant for changes in the physicochemical conditions of the medium, because it causes a movement of air in the soil more efficiently. Finally, we found that the parameters measured and the presence of local vegetation have an interdependent relationship and play a very significant role in ecosystem dynamics. Furthermore, we observed that the marked seasonality of the region and the factors which it ruled directly contribute to the oxidation of sulfides by changing the mineralogy and the physico-chemical properties of soil and interstitial waters of mangrove.